Exploring the impact of role-playing exercises on cognitive and emotional processes: a social- and educational psychological perspective - Löfstrand, Pär; Zakrisson, Ingrid (Frontiers in Psychology, 2025)
This study investigates the educational potential of role-playing exercises in addressing complex social phenomena such as attitude change, stereotyping, conformity, and racism. Building on prior research demonstrating the efficacy of role-play in reducing prejudice, this study aims to explore how such activities influence both cognitive and emotional engagement with these issues. The methodology included observation and evaluation of a professionally facilitated role-playing activity simulating the experience of being a refugee, conducted at an outdoor museum. Follow-up focus group interviews were conducted 2–3 years after the participants, students from local secondary schools engaged in the exercise. The findings indicate that the role-play had a lasting impact on students’ perceptions of forced migration and asylum seeking. Participants reported both cognitive insights and emotional responses, including empathy and personal reflection, as well as moments of detachment. The role-playing event was consistently described as one of the most memorable educational activities during their school years. A key implication from the evaluation and interviews is that, for role-playing to be an effective pedagogical tool in addressing sensitive topics such as xenophobia and prejudice, careful planning and structured facilitation are crucial to ensure meaningful and constructive outcomes.